Racial wage differentials in developed countries - Simonetta Longhi (IZA World of Labor, 2020)
In many developed countries, racial and ethnic minorities are paid, on average, less than the native white majority. While racial wage differentials are partly the result of immigration, they also persist for racial minorities of second and further generations. Eliminating racial wage differentials and promoting equal opportunities among citizens with different racial backgrounds is an important social policy goal. Inequalities resulting from differences in opportunities lead to a waste of talent for those who cannot reach their potential and to a waste of resources if some people cannot contribute fully to society.
Keywords: J7; J15; J31; 330; race; ethnicity; wage; inequality; discrimination